Kajian Empiris Efektifitas Program Peningkatan Kesejahteraan Melalui Pengelolaan Sampah - Tri Wahyu Hardaningrum (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Human treatment of waste that is not appropriate makes it have the worst connotation for human survival. Garbage will become a valuable item when humans can wisely manage it, and it is even possible to create alternative jobs that are prosperous. Organic and inorganic waste have added value for human life when they have been processed, both for economic survival and sustainable natural survival. This study seeks to examine the effectiveness of the welfare improvement program through waste management in the West Sumbawa Regency area. The research was conducted qualitatively with a phenomenological approach and 68 (sixty-eight) informants, consisting of local government officials, sub-district heads, traditional leaders, and several communities from all sub-districts in West Sumbawa Regency. The results showed that improving welfare through waste management was very effective, with a score of 82. Only a few areas located in hilly areas were not able to prosper through waste due to limited access and information. Through the existing program, the waste problem will be resolved in the short term, but in the long term it is necessary to empower the wider community in managing waste that produces economic value in the household and creates a new chain of improving people's welfare.